Performance of a cascade fertilizer seeder: sowing systems and mechanisms for fertilizer deposition - Ricardo Alves dos Santos, Paulo (Revista Ciência Agronômica, 2021)
It is necessary to use new technologies to mitigate water scarcity in the semi-arid region. As such, the aim ofthis study was to evaluate the operational and energy performance of a ridge planter and fertiliser, as well as the depositiondepth of maize seeds and fertiliser as a function of the sowing system, and the use of different furrowing mechanisms (discand shank) for depositing fertilisers. The experimental design was of randomised blocks, in a 6 x 2 factorial scheme withfour replications, including six sowing systems: (S 1 - intercropped ridge-sown maize; S2 – monocropped ridge-sown maize;S3 - intercropped furrow-sown maize; S4 – monocropped furrow-sown maize; S5 - conventional intercropping system; S6 -conventional monocropped system) and two mechanisms for depositing the fertiliser (offset double disc and shank furrower).The statistical analysis was carried out using the SISVAR software at 5% signifi cance. It was concluded that, irrespective ofthe sowing system (ridge or furrow) and mechanism employed, there is no difference in the initial plant population or in thedepth of the maize seeds. However, greater attention must be paid to the depth of both the fertiliser and forage seeds when theseare deposited at the same time. Sowing systems that turn the soil (furrow and ridge) consume more energy, as does the shankmechanism. Sowing system S5 affords better operating performance when used together with the disk mechanism.